Submandibular gland swelling: A diagnostic dilemma - Tarun Kumar; Gagan Puri; Aravinda Konidena; Deepa Patil (Wolters Kluwer Medknow Publications, 2014)
Submandibular swellings pose a diagnostic challenge to oral physicians, as many disease entities are involved in the differential diagnosis. Benign salivary gland tumors are one of them. Pleomorphic adenoma is the most common benign salivary gland tumor, which most commonly involves the parotid gland. Involvement of the submandibular gland is a rarity. This case report presents a rare case of a 60-year-old female patient with a unilateral submandibular swelling, diagnosed as a pleomorphic adenoma.